Competing or aligning? Assessment for Telecom operator's strategy to address OTT TV - Laili Aidi; Jan Markendahl; Konrad Tollmar; Greger Blennerud (International Telecommunications Society (ITS), 2012)
Up until recently, it was rarely direct competition between telecom operators, cable and satellite Pay-TV providers in digital TV/Video, as their business area were different and value chain was well established. However, technology advance has altered digital TV/Video landscape, made these Communication Service Providers (CSPs) cross other's area and opened door for new actor (OTT player) to enter the market. This triggers second change in the landscape, as it potentially bypasses CSP's role in digital media value chain. There are generic potential options for telecom operator to address OTT service's treat, where the trend shows gradual shifts toward allowing or promoting. This study assesses telecom operator's reaction strategies to react to this digital TV/Video convergence trend. Our analysis reveals two typical relation patterns in the value network, used by telecom operators based on strategy options above, which are point-to-point and point-to-multipoint relation model. We explore the underlining motivations that based these strategies, as well as analysis of the eco-systems: actors identification, business roles and distributed responsibilities among them, where we use ARA (Actors, Resource, Activities) point of view to model these value networks.
Keywords: 330; digital TV/Video; multimedia services; mobile broadband; business model